2017
DOI: 10.21825/vdt.v86i3.16287
|View full text |Cite
|
Sign up to set email alerts
|

De impact van advies omtrent het gebruik van antimicrobiële middelen op het voorschrijfgedrag in veertien Vlaamse praktijken voor kleine huisdieren

Abstract: A prospective study was performed to explore the prescription habits in fourteen first-line, small animal practices during first consultations of cats and dogs. Consultations one month prior to the implementation of antimicrobial use guidelines and at least 20 days thereafter were examined. Differences in the proportion of consultations during which antimicrobials were prescribed, were assessed. Additionally, changes in the choice of active substance were critically evaluated against the introduced antimicrobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 35 publications
(43 reference statements)
5
27
0
Order By: Relevance
“…Therefore, comparisons of AMU and AMR levels between countries and species should be interpreted while keeping in mind the restrictions of this small sample size. Nevertheless, the results did show similar trends with previous studies [25,26,28,[45][46][47][48] and enabled the identification of some significant differences, although some might be missed due to a lack of power. A recent Dutch study reported on the many different factors influencing the antimicrobial prescribing behavior of veterinarians [52].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Therefore, comparisons of AMU and AMR levels between countries and species should be interpreted while keeping in mind the restrictions of this small sample size. Nevertheless, the results did show similar trends with previous studies [25,26,28,[45][46][47][48] and enabled the identification of some significant differences, although some might be missed due to a lack of power. A recent Dutch study reported on the many different factors influencing the antimicrobial prescribing behavior of veterinarians [52].…”
Section: Discussionsupporting
confidence: 86%
“…More specifically, 36% of the total number of treatments was represented by CIAs of high priority, the other 35% were CIAs of the highest priority. Comparable results are highlighted in other studies investigating AMU in companion animals [25,26,28,[45][46][47][48]. A study in the UK, using data from 374 veterinary practices, reported similar proportions of CIAs usage, 60% in dogs and 81% in cats [49].…”
Section: Discussionmentioning
confidence: 53%
“…Indeed, in 41 per cent of cases, antimicrobial treatment was in partial or complete disagreement with national and international guidelines. These findings concur with studies in human and veterinary medicine showing that antimicrobials are commonly prescribed without clear indication,10 11 13 16 18 19 21 34 35 that HPCIAs are used as first-line agents12 15 23 and that adherence to general guidelines is often poor, both in hospital10 21 36 37 and first opinion practice settings 12 16 38. The results also concur with the situation in selected feline conditions in Switzerland where 38 per cent of antimicrobial treatments were found to be in in partial or total disagreement with consensus guidelines.…”
Section: Discussionsupporting
confidence: 84%
“…To date, only very few studies have investigated the impact of those guidelines on antimicrobial prescription in companion animals. A decrease of antimicrobial prescriptions after the introduction of prudent use guidelines has been reported in Flemish small animal practices and in a veterinary teaching hospital in Canada [9,36]. In a Europe-wide survey, veterinarians in countries with national policies for antimicrobial use, as for example Sweden, seemed to prescribe critically important antibiotics less frequently than in countries without such policies [11].…”
Section: Introductionmentioning
confidence: 99%
“…A One Health approach is required to combat the development and spread of antimicrobial-resistant bacteria [1,2]. Antimicrobial use is thought to be a major driving force towards antimicrobial resistance [3,4] and overprescription of antimicrobials seems to be common in human and veterinary medicine [5][6][7][8][9]. The largest proportion of antimicrobials sold in Europe are used to treat food producing animals and the role of companion animals in this context has been neglected for a long time [10].…”
Section: Introductionmentioning
confidence: 99%